KEBIJAKAN CHINA MELAKUKAN KERJASAMA ENERGI MINYAK DENGAN SUDAN (2009-2012) - Indah Rahmayeni (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
China is one of the countries in Asia that have the highest energy needs and is the country with the most influential economic force. China did a lot of cooperation with the countries in the world. China's presence in Sudan beginning with the Chinese presence in Africa and cooperation undertaken. China formally perfect relationship with Africa in the presence of Hu Jintao's visit to various city African countries. To exert this study, the writer make the research questions are: Why does China conduct cooperation on oil energy with Sudan in 2009-2012.The method used in this study is qualitative. Qualitative research can be defined as a series of activities or processes to capture information on reasonable conditions in the life of an object, connected with solving a problem, both from a theoretical and practical point of view. Research techniques used in this study is a secondary data collection techniques based literature known as the research literature (literary research).Various policies issued by China, especially in matters of aid loans to economic sectors and even the military, many advantageous for Sudan, due to the Chinese principle of non-intervention of the assistance provided by the Chinese, tend not much demand and free requirements unless the cooperation that exists between China and Sudan in the processing of energy resources, especially oil Sudan. But it turns out a lot of Chinese foreign policy, especially regarding financial aid issues for African countries that have drawn criticism from various international parties. China's foreign policy related to the process of finding and securing its energy consists of three main elements that consist of: great power diplomacy, good neighbor or peripheral diplomacy, and energy or resource diplomacy. Cooperation of China and Sudan as a form of investment policy implemented through state-owned companies namely CNPC (China National Petroleum Corporation), the realization of cooperation in the field of investment.Keywords: Policies, Oil Energy, Cooperation